Students Empowerment through the Cultivation of Family Medicinal Plants: Cultivation of Family Medicinal Plants - EKASARI, RANTI; Widiastuty, Lilis; Bujawati, Emmi; Guhir, Faradila; Maharani (Institute for Research and Community Services, 2024)
Medicinal plants are used by millions of people around the world. The medicinal plants chosen are usually plants that are interchangeable for first aid. The existence of medicinal plants is very important, especially for families who do not have easy access to medical services such as clinics, health centers or hospitals. The aim of this research is to increase the knowledge and health of school residents by drawing air from healthy Family Medicinal Plants or well known as TOGA and as first aid in case of minor health problems. Empowerment activities were carried out at SMK BAZNAZ, South Sulawesi on March 4-7 2022 using the Asset Based Community Developments (ABCD) method. Based on the results of the questionnaire, it was concluded that TOGA implementation counseling had an increase in knowledge in class 10 students at SMK BAZNAS and the results of interviews with informants stated that they wanted to hide TOGA in the surrounding environment considering the many benefits of family medicinal plants. It is suggested to the school to continue running the TOGA cultivation program at school. Apart from that, the school also provides special land for cultivating TOGA because the school in question also has a pharmacy major. Hopefully in the future this TOGA can be useful for pharmacy majors.